1989
DOI: 10.1128/iai.57.10.3131-3135.1989
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of endotoxin fever in rabbits by using a monoclonal antibody to tumor necrosis factor (cachectin)

Abstract: A murine monoclonal antibody to rabbit tumor necrosis factor (TNF; cachectin) was injected intravenously into an endotoxin-treated rabbit to examine the role of endogenous TNF in fever. Both early and late peaks of biphasic fever evoked by the endotoxin injection were suppressed by the antibody. TNF activity was detected in an endotoxin dose-dependent manner in the blood 1 h after the endotoxin injection, which was coincident with the early-peak fever. Although the late-peak fever responded to the antibody, no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

1990
1990
2003
2003

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…administration of TNF‐ α induces fever in rats 41 and in rabbits 42 and i.v. injection of monoclonal antibody to TNF in rabbits reduces the LPS‐induced biphasic fever 43 . These results suggest that LPS induces fever through the release of TNF‐ α at the central level.…”
Section: Discussionmentioning
confidence: 71%
“…administration of TNF‐ α induces fever in rats 41 and in rabbits 42 and i.v. injection of monoclonal antibody to TNF in rabbits reduces the LPS‐induced biphasic fever 43 . These results suggest that LPS induces fever through the release of TNF‐ α at the central level.…”
Section: Discussionmentioning
confidence: 71%
“…10 ng (5 ng/kg) ofrrllr1a was required to induce significant and consistent CSF pleocytosis (CSF WBC >1,000/mm 3) in our model, the same quantity of rrIIr10 that was shown to be necessary to elicit a febrile response when injected intravenously into rabbits (43). Likewise, Kawasaki et al (34) RaTNF-a evoked a monophasic febrile response, and that 3 x 104 IUlkg was required to produce a biphasic febrile reaction. In our experiments, significant and consistent CSF pleocytosis was attained after intracisternal inoculation of -104 IU of the same preparation .…”
Section: Discussionmentioning
confidence: 96%
“…Actually, there are several reports in which the injection of TNF-␣ produced fever in human and experimental animals (30,37). In addition, polyclonal and monoclonal antibodies against TNF-␣ (anti-TNF) have been found to attenuate lipopolysaccharide (LPS)-and turpentine-induced fever (4,18,29). However, Long et al (26) have shown opposite results, that is, anti-TNF further enhanced LPS-induced fever, and Klir et al (21) have reported that intraperitoneal injection of human recombinant TNF-␣ attenuated LPS-induced fever in rats.…”
mentioning
confidence: 99%